Association between a polymorphism in the human programmed death-1 (PD-1) gene and cytomegalovirus infection after kidney transplantation. Issue 1 (5th July 2009) - Hoffmann, Thomas W; Halimi, Jean-Michel; Büchler, Mathias; Velge-Roussel, Florence; Goudeau, Alain; Al-Najjar, Azmi; Marliere, Jean-Frédéric; Lebranchu, Yvon; Baron, Christophe
Abstract : Background: Cytomegalovirus (CMV) infection is the most frequent infectious disease following organ transplantation. Strategies to prevent this infection remain a matter for debate, and discovering genetic risk factors might assist in adapting preventive strategies. By inhibiting IFNγ production, programmed death 1 (PD-1) has a crucial role in anti-CMV immune response. A single nucleotide polymorphism (SNP) within intron 4 of the gene (rs11568821), called PD-1.3, has recently been reported to be clinically relevant in several immune disorders. However, its association with CMV infection has never been reported. Methods: In this study, the risk of CMV infection according to PD-1.3 genotype was investigated in 469 kidney graft recipients transplanted between 1995 and 2005. Results: It was found that the A allele was associated with the risk of CMV infection in seropositive patients who did not receive CMV prophylaxis (OR=2.60, p=0.006). Multivariate analysis including other risk factors for CMV infection showed that this allele was independently associated with CMV infection (OR=2.54; p=0.010). Interestingly, combined analysis of PD-1.3 with the IL12B 3′UTR SNPs (previously shown to be associated with CMV infection) revealed that patients with the PD-1.3 A allele had a much higher risk of CMV infection compared to those having neither risk allele (OR=3.76; p=0.0003). Conclusion: This study identified a new genetic risk factor for CMV infection after kidney transplantation and suggests that an adjustment of CMV prophylaxis based on genetic markers would merit further investigation.